Pelatihan Pembukuan Sederhana Bagi Pelaku UMKM di Desa Kore, Kecamatan Sanggar - Alwi, Alwi; Rimawan, M.; Ismunandar, Ismunandar; Hidayanti, Mawar (CV. Devi Tara Innovations, 2024)
Micro and small businesses that withstand economic crises are able to absorb labor thereby significantly reducing unemployment. In Kore Village, Sanggar District, Bima Regency, small and medium-sized businesses often neglect accounting, and there is no separation of personal and business assets. Most of these MSME actors are still making decisions based on intuition and experience. In simple accounting training for small businesses, the purpose of implementing PKM is to know how to do accounting itself so that it is systematic and important when doing accounting so that income, costs and profits are measured. and know the development of the business. In Kore Baru Village, Sanggar District, Bima Regency, the method of implementing community service is divided into three stages, namely the first stage of interviews and field observations, the second stage of conducting training, and the last stage is mentoring and monitoring. . The results obtained from this activity are able to increase knowledge and skills in business management through simple and easy-to-implement bookkeeping/accounting so as to increase work motivation.